2020
DOI: 10.1017/s1478951520001066
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of distress in patients with advanced cancer: A retrospective study

Abstract: Objective The objective of this study was to assess the psychosocial distress and associated factors in advanced cancer patients consulting at the outpatient Palliative Care Unit at the National Cancer Institute in Mexico City. Design A retrospective study was conducted using electronic records (June 2015 to December 2016). Sample A total of 646 patients with advanced cancer during their first visit to the outpatient palliative care unit at the National Cancer Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
(60 reference statements)
0
9
1
Order By: Relevance
“…Fatigue, feeling swollen, pain, eating difficulties, worrying and feeling nervous, or loss of interest, were the main problem items significantly related to psychological distress in Gazan patients. A retrospective study in Mexico City has also reported that the psychological distress of patients with advanced cancer was significantly associated with transportation (Ascencio-Huertas et al, 2021). This was not found in this study, which may be related to the availability of support from non-governmental organizations covering transportation expenses for patients with cancer in Gaza, alongside the short distances travelling to hospitals in the GS.…”
Section: Discussioncontrasting
confidence: 70%
“…Fatigue, feeling swollen, pain, eating difficulties, worrying and feeling nervous, or loss of interest, were the main problem items significantly related to psychological distress in Gazan patients. A retrospective study in Mexico City has also reported that the psychological distress of patients with advanced cancer was significantly associated with transportation (Ascencio-Huertas et al, 2021). This was not found in this study, which may be related to the availability of support from non-governmental organizations covering transportation expenses for patients with cancer in Gaza, alongside the short distances travelling to hospitals in the GS.…”
Section: Discussioncontrasting
confidence: 70%
“…Fifteen studies observed relationships between individual reported sources of CRD and reporting actionable levels of CRD severity. Emotional concerns of sadness, 23 , 24 , 34 , 35 , 36 , 37 , 42 , 45 , 53 , 61 , 64 , 68 nervousness, 24 , 35 , 36 , 41 , 42 , 44 , 45 , 53 , 61 , 64 , 68 depression, 23 , 34 , 35 , 37 , 41 , 42 , 44 , 53 , 61 , 64 fears, 23 , 35 , 37 , 42 , 44 , 45 , 53 , 61 , 64 , 68 worry, 23 , 34 , 35 , 37 , 42 , 45 , 53 , 61 , 64 ...…”
Section: Resultsmentioning
confidence: 99%
“…Frequently patients have to rent private transportation and travel for long distances to access HCPs. Thus, patients may experience physical discomfort, time consumption and high costs which contribute to psychological distress 40 .…”
Section: Discussionmentioning
confidence: 99%